Significantly Longer Envelope V2 Loops Are Characteristic of Heterosexually Transmitted Subtype B HIV-1 in Trinidad - Collins Fairclough, Aneisha (2011)
Background In Trinidad and the wider Caribbean, subtype B Human Immunodeficiency Virus-type 1 (HIV-1B) overwhelmingly accounts for HIV infection among heterosexuals; this contrasts with the association of HIV-1B with homosexual transmission and injecting drug use globally. The HIV envelope contains genetic determinants of cell tropism and evasion from immune attack. In this study we investigate the genetic properties of the env V1-C4 of HIV-1B soon after transmission to Trinidadian heterosexuals. This will reveal distinctive genetic features of the strains that cause the HIV-1B epidemic in Trinidad and generate insights to better understand their properties. Methodology/Principal Findings Quasispecies sampling was performed on the env V1-C4 of HIV-1B strains soon after transmission to heterosexual Trinidadians in a cohort of seroconverters. Phylogenetic relationships were determined for these quasispecies and the length and number of asparagine (N) linked glycosylation sites (NLGS) in their variable loops compared to that for HIV-1B globally. Signature amino acids within the constant domains of the env V1-C4 were identified for heterosexually transmitted HIV-1B from Trinidad relative to HIV-1B globally. HIV-1B obtained from Trinidadian heterosexuals soon after seroconversion had significantly longer V2 loops with one more glycosylation site, shorter V3 loops and no significant difference in V1 or V4 when compared to HIV-1B obtained soon after seroconversion from infected individuals in the rest of the world. HIV-1B soon after seroconversion and during chronic infection of Trinidadians was not significantly different, suggesting that distinctly long V2 loops are characteristic of HIV-1B in Trinidad. A threonine deletion at position 319 (T319-) along with the substitutions R315K and S440R were found to be distinctly associated with HIV-1B from Trinidad compared to HIV-1B globally. Conclusions This finding of distinctive genetic features that are characteristic of HIV-1B strains from Trinidad is consistent with the Trinidad epidemic being established by a founder strain or closely related founder strains of HIV-1B.